2013
DOI: 10.1371/journal.pone.0076691
|View full text |Cite
|
Sign up to set email alerts
|

Are Patient Views about Antibiotics Related to Clinician Perceptions, Management and Outcome? A Multi-Country Study in Outpatients with Acute Cough

Abstract: BackgroundOutpatients with acute cough who expect, hope for or ask for antibiotics may be more unwell, benefit more from antibiotic treatment, and be more satisfied with care when they are prescribed antibiotics. Clinicians may not accurately identify those patients.ObjectiveTo explore whether patient views (expecting, hoping for or asking for antibiotics) are associated with illness presentation and resolution, whether patient views are accurately perceived by clinicians, and the association of all these fact… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
99
1
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 105 publications
(108 citation statements)
references
References 31 publications
7
99
1
1
Order By: Relevance
“…This study was not a clinical trial, and the groups were not assigned randomly. The percentage of physicians who stated that subjects had requested an antibiotic was very low in our study (only 1.4%), being much lower than what was reported by Coenen et al, 13 who observed a percentage of 10.2% in a study involving nearly 3,500 adult subjects with acute cough in 14 different European networks. In our study, approximately one third of the infections included corresponded to the common cold; in these cases, the request for an antibiotic was unlikely.…”
Section: Discussioncontrasting
confidence: 84%
See 1 more Smart Citation
“…This study was not a clinical trial, and the groups were not assigned randomly. The percentage of physicians who stated that subjects had requested an antibiotic was very low in our study (only 1.4%), being much lower than what was reported by Coenen et al, 13 who observed a percentage of 10.2% in a study involving nearly 3,500 adult subjects with acute cough in 14 different European networks. In our study, approximately one third of the infections included corresponded to the common cold; in these cases, the request for an antibiotic was unlikely.…”
Section: Discussioncontrasting
confidence: 84%
“…[9][10][11] There is compelling evidence that patients' satisfaction with the consultation is not affected by prescribing of antibiotics, and patient dissatisfaction has been shown to be significantly related only to poor communication between the patient and the doctor. 12,13 Despite numerous papers on patients' expectations and physicians' perceptions and their impact on antibiotic prescribing for respiratory tract infections, few studies addressing the explicit request for antibiotics by patients during the consultation have been published. GPs often prescribe an antibiotic to fulfill patient demands in an attempt to satisfy the patient.…”
Section: Introductionmentioning
confidence: 99%
“…However, perceptions are not always accurately aligned with patient expectations (27,45). Interestingly, in the study by Coenen et al, patients explicitly asking for antibiotics (as reported by the patient) did not have a significant effect on prescribing, and there was a trend toward reduced prescribing, in contrast to the physician perceiving that a patient was expecting an antibiotic, which was associated with prescribing (44). This suggests that by asking, the patient addresses directly the issue at hand, allowing for a discussion to ensue regarding the need for antibiotics.…”
Section: Discussionmentioning
confidence: 94%
“…Just over half of the included studies were from the United States (n ϭ 15) (11,20,21,24,26,28,30,31,33,(38)(39)(40)(45)(46)(47), with the remainder from Canada (n ϭ 3) (34,37,43), The Netherlands (n ϭ 2) (29,35), Germany (n ϭ 2) (23, 42), Italy (n ϭ 1) (27), the United Kingdom (n ϭ 1) (25), Belgium (n ϭ 1) (22), and a network of 13 European countries (n ϭ 3) (36,41,44). Eight of the U.S. studies used the NAMCS (National Ambulatory Medical Care Survey) or NHAMCS (National Hospital Ambulatory Medical Care Survey) data sets for their analyses (11,28,31,33,(38)(39)(40)46).…”
Section: Resultsmentioning
confidence: 99%
“…12,26,27 Whether the responses to these items reflect lower parent-provider trust would be important to determine in order to find ways to meet patients' needs while still decreasing unnecessary antibiotic use. 43 The survey included assessment of sources parents rely on for their medical information. Across insurance type, parents place high trust in their health care providers.…”
Section: Discussionmentioning
confidence: 99%